Togo Digital Economy Diagnostic Report - World Bank Group (World Bank, Washington, DC, 2021)
Rapid digital transformation has been re-shaping the global economy, changing fundamental patterns of socioeconomic activities and accelerating further in the wake of the global Coronavirus (COVID-19) pandemic. In this context, relying on the Digital Economy for Africa (DE4A) methodology, the report conducts a timely diagnostic of the state of digital economy in Togo. Togo is bordered by Ghana, Benin, and Burkina Faso, and has a coastline that runs along the Gulf of Guinea. The government of Togo (GoT) is cognizant of the importance of the transformation towards a digital economy. As the government of Togo launches into the development of a new strategy for digital transformation “Togo Digital 2025” the current diagnostic would provide useful information to use as a basis for such strategic document. This report aims to highlight opportunities to further develop Togo’s digital economy with a special focus on policies that can bridge the digital divide and help Togo achieve the DE4A targets. This report aims to provide practical and actionable recommendations that inform decision makers on priority areas for development.